Different School Reopening Plans on Coronavirus Disease 2019 Case Growth Rates in the School Setting in the United States. (25th March 2021) - Liu, Dong; Lin, Ge; Sun, Xiaoting; Du, Yi; Liu, Han; Qu, Ming
Abstract : BACKGROUND: In fall 2020, all public K‐12 schools reopened in broadly 3 learning models. The hybrid model was considered a mid‐risk option compared with remote and in‐person learning models. The current study assesses school‐based coronavirus disease 2019 (COVID‐19) spread in the early fall using a national data set. METHODS: We assess COVID‐19 case growth rates from August 10 to October 14, 2020 based on a crowdsourcing data set from the National Education Association. The study follows a retrospective cohort design with the baseline exposures being 3 teaching models: remote learning only, hybrid, and in‐person learning. To assess the consistency of our findings, we estimated the overall, as well as region‐specific (Northeast, Midwest, South, and West) and poverty‐specific (low, mid, and high) COVID‐19 case‐growth rates. In addition, we validated our study sample using another national sample survey data. RESULTS: The baseline was from 617 school districts in 48 states, where 47% of school districts were in hybrid, 13% were in remote, and 40% were in‐person. Controlling for state‐level risk and rural‐urban difference, the case growth rates for remote and in‐person were lower than the hybrid (odds ratio [OR]: 0.963, 95% confidence interval [CI]: 0.960‐0.965 and OR: 0.986, 95% CI: 0.984‐0.988, respectively). A consistent result was found among school districts in all 4 regions and each poverty level. CONCLUSIONS: Hybrid may not necessarily be the next logical option when transitioning from the remote to in‐person learning models due to its consistent higher case growth rates than the other 2 learning models.